Measuring and Manipulating Constitutional Evaluations in the States: Legitimacy Versus Veneration. Issue 5 (September 2019) - Brown, Adam R.; Pope, Jeremy C.
American civil religion places the U.S. Constitution on a pedestal. Although this veneration is well-documented, it is unclear where it originates and why other constitutions do not attract the same reverence. We develop a measure of constitutional respect and conduct a randomized survey experiment testing whether new information can change respondents' evaluations of their state or national constitutions. We find that people do respond to new information about state constitutions, but not to information about the national document, suggesting that Americans view the U.S. Constitution with the sort of veneration and reverence James Madison advocated, while viewing their state constitutions through a more Jeffersonian lens of legitimacy, one that favors continually revising these constitutions to meet the living generation's needs.